Enhancing the Mutation Testing Education through a Gamified Environment - Darienço, Dário; Oliveira, Alessandreia Marta de; Vilela, Ricardo Ferreira; Silva, Williamson; Arimoto, Maurício Massaru; Valle, Pedro Henrique (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2026: Anais do VI Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2026.18661, 2026)
Software testing plays a central role in quality assurance. However, challenges remain in teaching advanced concepts, such as mutation testing. The literature suggests that traditional methods do not always effectively support student engagement, motivating the adoption of active learning approaches. We present GAMutation, a gamified environment developed with the Construct 2 to support the teaching of mutation testing. To evaluate its usability, a heuristic evaluation was conducted with undergraduate students. The results indicated positive perceptions and highlighted aspects of the interface and interaction that may guide future improvements. The study reinforces the potential of gamification as a complementary strategy in software testing education.